-الإدارة الإلكترونية ودورها في تحسين الخدمة العمومية دراسة حالة وحدة بريد الجزائر بلدية إبن الناصر ابن شهرة-الأغواط - بن بوزيد خديجة; الجوبر عائشة; خنيش يوسف (جامعة عمار ثليجي الاغواط, 2021)
Electronic management has become the backbone of modern societies, and an imperative necessity that must be sought to be applied in all institutions, in order to keep pace with technological progress such as communications, and electronic management has played an important role in improving public services provided to citizens through speed of delivery, such as perfection in service, accuracy and effectiveness, In addition to reducing procedures in completing transactions, and facilitating communication between the citizen and his administration. In order to ensure the service of electronic administration, it is necessary to spread an electronic culture of services among citizens, and to restore the infrastructure of institutions in accordance with what is compatible with the modern environment. Where this study aims to research the various aspects of electronic administration and its role in improving the public service, which has become the focus of all administrative institutions and others. Through this study, we tried to shed light on the most important applications of electronic management that depend on information technology, such as communications, especially the Internet, as the most important means adopted by the administration in providing services on the one hand, and one of the most technologies that citizens resort to when they wish to obtain service on the other hand. The study was conducted in the township of Ibn Al-Nasser Ibn Shahra, the wilaya of Laghouat, on the director of the Algeria Postal Unit, which is located at the township level.